Consumer attitude and preference in the Islamic mortgage sector: a study of Malaysian consumers - Amin, H; Rahman, ARA; Razak, DA; Rizal, H (EMERALD GROUP PUBLISHING LTD, 2024)
Purpose - The purpose of this study is to investigate the effects of service quality, product choice and Islamic debt policy on consumer attitude within the context of Islamic mortgage sector in Malaysia. The present study also examines the effect of attitudinal-behaviour on consumer preference towards preference of Islamic mortgage selection. Design/methodology/approach - The study is based on questionnaire survey. Data are collected using sample from customers of Islamic banks in Malaysia. The study collects 351 respondents. Data are analysed using partial least squares (PLS). Findings - The results indicate that service quality, product choice and Islamic debt policy significantly influence consumer attitude, in turn, affecting the Islamic home financing preference. Consumer attitude also mediates the effects of service quality, product choice and Islamic debt policy on the Islamic home financing preference. Research limitations/implications - Several limitations warrant future research. First, this study considers only a specific user group in one public university. Second, this study does not consider attitude as a moderator. Third, this study suffers from the limited number of factors used. These limitations, however, provide directions for future research. Practical implications - Our results will add value to the consumer preference topic for Islamic home financing literature. The present study provides bank managers with valuable insights into better planning of Islamic home financing services in Malaysia. Originality/value - This study is a pioneering effort at exploring consumer attitude and preference from the context of Islamic mortgage sector in Malaysia. The use of PLS analysis provides another important contribution to the literature in this area.